AN INVESTIGATION OF THE ADSORPTION AND DECOMPOSITION OF PH3 AND NH3 ON GAAS(100) - Singh, N; Murrell, A; Foord, J (1992)
The adsorption and thermal decomposition of PH3 and NH3 on the Ga-rich GaAs(100)-(4 × 1) surface has been studied using temperature programmed desorption (TPD), Auger electron spectroscopy (AES) and high resolution electron loss spectroscopy (HREELS) techniques. At room temperature PH3 was found to chemisorb on the GaAs surface and HREELS and isotopic scrambling experiments using deuterium suggest the major species present is PH2. Electron beam irradiation brings about complete dissociation to form phosphorus on the surface which is stable for temperatures up to 800 K, at which point desorption of P4 takes place. Adsorption at 140 K shows three adsorption states. At low coverages adsorption into two chemisorbed PH2 states occurs; at higher coverages a molecularly bound PH3 state exists which reversibly desorbs at low temperatures as the temperature is raised. Adsorption of NH3 at 150 K yields two clearly resolved NH3 desorption peaks. However, HREELS indicates that both arise as a result of molecular adsorption state. The lower temperature peak is due to the physisorbed state while the higher temperature peak (250-350 K) is associated with desorption of the chemisorbed phase. Some thermal cracking of NH3 on the surface takes place giving rise to NH2 and H species as shown by HREELS and coadsorption experiments with deuterium. These species undergo recombinative desorption at high temperatures although trace amounts completely decompose to produce surface N. Electron beam irradiation at energies as low as 10 eV was also observed to result in decomposition of the adsorbed molecular phases. © 1992.